Light-triggerable delivery of a gene edition system - Rebelo, Catarina Araújo Gomes (2020)
Advancements in sequencing technologies have now set the pace on applying the resulting information of our genome into a more clinical relevant output. Gene editing, with the ability to change genomic DNA in a targeted manner, has gained an important spot in the nextgeneration of advanced therapies. Moreover, spatio-temporal control of gene expression may provide an unprecedent understanding of the relevance of specific genes in biological processes as well as a triggerable tool to modulate cell activity. The main objective of this thesis was to develop nanoformulations for the light-responsive delivery of gene editing enzymes, particularly Cre recombinase. During the last years, the scientific community has done considerable efforts in the development of delivery strategies for the clinical translation of gene editing systems. From the different possibilities, non-viral delivery of protein or mRNA cargos is likely a safer and more efficient strategy. With this purpose we have developed two different nanocarriers each with different specificities. The first nanocarrier was based on lanthanide-doped upconversion nanocrystals (UCNPs) that converts NIR into blue light. A photocleavable linker able to attach in one end the UCNP and in the other end the Cre recombinase enzyme, while maintaining its enzymatic activity, allowed the NIR-light mediated delivery of the enzyme. In addition to Cre, the surface of UCNPs was modified with hydroxychloroquine to facilitate NP endolysosomal escape. The formulation was more efficient than conventional transfection agents (RNAiMAX) and other reported nanocarriers for the intracellular delivery of Cre, requiring less protein to achieve similar functional protein delivery levels. This nanocarrier was evaluated in vivo, in the setting of the brain, as a transcranial NIR gene editing system for deep brain regions including the subventricular zone and the ventral tegmental area. Results showed that the level of recombination obtained was sufficient to induce functional responses in the living animals. Although mRNA offers several advantages over protein or DNA delivery (straightforward production and transient expression), the successful delivery of this large anionic molecule is still very challenging. To obtain a biocompatible delivery of Cre mRNA, we took advantage of a lightsensitive polymeric library of 160 polymers that was previously reported by us for the identification of agents with transfections comparable to the commercial agents. We performed a highthroughput study for the identification of vectors with chemical diversity that could transfect mRNA. We could identify 7 candidates that, although not yet optimized for light-mediated expression of Cre enzyme, are UV/blue-light responsive. The candidates were able to rapidly transfect (10 min) a reporter cell line with Cre mRNA and obtain, in this condition, recombination levels up to 50% for the tested formulations.